Riociguat in patients with chronic thromboembolic pulmonary hypertension: results from an early access study - McLaughlin, Vallerie V.; Grünig, Ekkehard (BMC pulmonary medicine, 2017)
Following positive results from the Phase III CHEST-1 study in patients with inoperable or persistent/recurrent chronic thromboembolic pulmonary hypertension (CTEPH), the Phase IIIb CTEPH early access study (EAS) was designed to assess the safety and tolerability of riociguat in real-world clinical practice, as well as to provide patients with early access to riociguat before launch. Riociguat is approved for the treatment of inoperable and persistent/recurrent CTEPH.